Analysis of Teaching Computer Programming in Indian Context - Chenna Reddy, P. (Journal of Engineering Education Transformations, 2015)
Engineering education is given significant importance in India. A fundamental component of a computer science and engineering curriculum is computer programming and is generally studied at first year under-graduation. It is not only a difficult course but is the basic course which can affect the student prospects in the entire engineering program. It places the student in a groove and enables him to move along the correct path. Unfortunately engineering education in India is going through a turbulent period and there is need to correct it. Programming is a subject which has become essential across the disciplines. This paper analyses the reasons for the difficulties experienced by first year programming students, reviews current methods of teaching programming, identifies effective ways of teaching programming, and provides guidelines to fine tune teaching programming to individual requirements. It assumes Indian environment.